Analysis of Flexibility and Balance on Acceleration of Racehorse Jockeys in Jeneponto Regency (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the relationship between jockeys' physical conditions, namely flexibility and balance, to the acceleration of racehorse jockeys in Jeneponto Regency. The method used is Ex Post Facto with a Descriptive Correlational Path Analysis approach. The study population includes all racehorse jockeys in Jeneponto Regency, with a sample of 30 jockeys taken using the total sampling method. The research instruments consist of a flexibility test, a dynamic balance test, and a track travel time test to measure acceleration. Data were analyzed through correlation tests and path analysis. The results of the analysis show: (1) There is a significant relationship between jockeys' flexibility and acceleration (r = 0.714), which explains 71.4% of the variance in acceleration. (2) Balance also shows a significant relationship with acceleration (r = 0.751), explaining 75.1% of the variance in acceleration. (3) Simultaneously, flexibility and balance have a significant relationship (r = 0.754), with R² = 0.568, meaning that 56.8% of jockey acceleration can be explained by these two variables. The conclusion is that 56.8% of a racehorse jockey's acceleration is explained by the contribution of flexibility and balance. Physical conditions in the form of flexibility and balance are dominant and important factors that support each other in determining a jockey's ability to produce optimal acceleration on a racehorse.